Growth and fatty acid distribution over lipid classes in Nannochloropsis oceanica acclimated to different temperatures - Ferrer-Ledo, Narcís; Stegemüller, Lars; Janssen, Marcel; Wijffels, René H.; Barbosa, Maria J. (Frontiers in Plant Science, 2023)
After light, temperature is the most relevant environmental parameter in outdoors cultivation of microalgae. Suboptimal and supraoptimal temperatures negatively impact growth and photosynthetic performance with a subsequent effect on lipid accumulation. It is generally recognised that lower temperatures trigger an increase in fatty acid desaturation while higher temperatures trigger the opposite reaction. The effect of temperature on lipid classes has been less studied in microalgae and in certain cases, the effect of light cannot be completely excluded. In this research, the effect of temperature on growth, photosynthesis, and lipid class accumulation in Nannochloropsis oceanica was studied at a fixed light gradient with a constant incident light intensity (670 μmol m-2 s-1). A turbidostat approach was used to achieve temperature acclimated cultures of Nannochloropsis oceanica. Optimal growth was found at 25-29°C, while growth was completely arrested at temperatures higher than 31°C and lower than 9°C. Acclimation to low temperatures triggered a decrease in absorption cross section and photosynthesis rates with a tipping point at 17°C. Reduced light absorption was correlated with a decrease in content of the plastid lipids monogalactosyldiacylglycerol and sulfoquinovosyldiacylglycerol. The increase of diacylglyceryltrimethylhomo-serine content at lower temperatures indicated a relevant role of this lipid class in temperature tolerance. Triacylglycerol content increased at 17°C and decreased at 9°C emphasising a metabolic switch in stress response. Total and polar eicosapentaenoic acid content remained constant at 3.5 and 2.4% w/w, despite the fluctuating lipid contents. Results show an extensive mobilisation of eicosapentaenoic acid between polar lipids classes at 9°C to ensure cell survival under critical conditions.